Utopian Visions in Cold War Documentary : Joris Ivens, Paul Robeson and Song of the Rivers (1954) - Musser, Charles (Cinémas, 2002)
Abstract This essay reconsiders several documentary projects in film and photography that sought to articulate utopian possibilities at the height of the Cold War, when ideological imperatives constrained artists of all political persuasions. The central art work is Joris Ivens’ Song of the Rivers (1954), which is analysed and then juxtaposed to Edward Steichen’s Family of Man (1955) photography exhibition. In seeking to reclaim the textual complexity and dialectics of Ivens’ work, this analysis looks at the personal narratives that are threaded through the film’s epic aspirations. Involving Ivens and Paul Robeson, these narratives mobilize the trope of the river that recurs in both Soviet film and Robeson’s performances. Ivens and Robeson both returned to, and so refigured, elements of Song of the Rivers in two much smaller and more intimate film projects : Ivens’ La Seine a rencontré Paris ( The Seine Meets Paris, 1957) and Robeson’s Brücke über den Ozean ( Bridge Over the Ocean, 1958), made with Earl Robinson.